The Federal Republic in the North-South dialogue: Some longerterm projections - Lothar Hübl; Klaus-Peter Möller (Intereconomics, 1978)
For some time now the Federal Republic of Germany has been the largest exporter in the world, with a slight lead over the USA and some way ahead of Japan and the Soviet Union. It has therefore an important role to play in the North-South dialogue. The increasing mutual dependence of the Federal Republic and the developing countries is described by different scenarios in the following article.
Keywords: 330; Scenarios